Effects of Neonatal Feeding Patterns on Infant Health - Shi Xiaoli; Hao Weiyan; Dandan Li (Applied Bionics and Biomechanics)
Objective. Early and reasonable feeding mode can not only ensure the good nutritional condition of infants but also enhance the infant immunity and resistance, which has a certain role in promoting health and preventing the occurrence of chronic diseases in adulthood. In this study, the effect of neonatal feeding methods on the infant body, the influence of early feeding on the growth rate, and development of infants aged 0-3. Method. From January 2016 to June 2019, a total of 600 infants who have been systematically managed in our hospital since birth were selected. All newborns were 37-40 weeks old, weighing 2350-4100 g, without congenital diseases. They were grouped according to feeding methods. 194 infants were exclusively breastfed, 32.3%; 207 people were artificially fed, 34.5%; 199 people were mixed fed, 33.2%. The Kaup index method was used to judge the nutritional status. Developmental Screening Test for ages 0 to 6 (DST) and Bailey Infant Development Scale (BIDS) were used to rate the intellectual and behavioral development of infants and children. According to the growth and development reference standard of 0 ~ 4-year-old children recommended by who in 2006, the age weight standard deviation score (WAZ), age length (height) standard deviation score (HAZ), and body (long) height-weight standard deviation score (WHZ) were performed, and the statistical analysis was performed with SPSS24.0 software. The height, weight, intelligence, and motor development of infants in the three groups at 1 month, 3 months, 6 months, 12 months, 24 months, and 36 months were analyzed and compared, and the test results were recorded in detail. Result. There was no significant difference in 3-month-old WAZ and HAZ among the three groups (P>0.05). Within 6 months, the WAZ and HAZ values of the pure breastfeeding group and mixed feeding group were higher than those of the artificial feeding group (P<0.05). From 6 months to 12 months, the WAZ and HAZ values of the artificial feeding group were better than those of artificial feeding group and mixed feeding group (P<0.05). The scores of MI, DQ, PDI, and MDI in the mixed feeding group within 12-36 months were slightly higher than those in the breastfeeding group and significantly better than those in the artificial feeding group (P<0.05). The prevalence of the breastfeeding group was 22.2% (43/194) and mixed feeding group was 19.8% (39/199), which was lower than that of the artificial feeding group 57.8% (120/207), P<0.01. The number of people with normal psychological development was 88.7% (172/194) in the breastfeeding group and 88.9% (177/199) in the mixed feeding group, which was higher than 76.3% (158/207) in the artificial feeding group (P<0.01). Conclusion. When there is little colostrum secretion in the first 2-3 days of delivery, appropriate addition of formula milk can reduce the incidence of diseases in newborn infants. Breast milk is the most perfect natural food. The immune substance in breast milk is an important element for infants to resist diseases. The communication between mother and child is the first condition for the development of infant mental health.